Study of Chelating Tendency of Serine by Ionophoretic Technique - Agarwal, Shashi; Singh, Satyendra (Asian Journal of Chemistry, 2010)
A method involving the use of paper electrophoresis is described for the study of equilibria in mixed-ligand complex systems in solution. The technique is based on the movement of a spot of metal ion under an electric field with the complexants added to the background electrolyte at pH 8.5. The stability constants of the complexes were found to be 6.31, 5.14 and 5.01 (log K values) for Th(IV), Cr(III) and Al(III) complexes, respectively, at μ = 0.1 and 35 ºC.